Expressões faciais de emoções de crianças com deficiência visual e videntes: avaliação e intervenção sob a perspectiva das Habilidades Sociais - Ferreira, Bárbara Carvalho (2012)
The ability of expressing emotions via facial expressions is an indispensable component of some required childhood social skills. Therefore, facial expressions are crucial for successful social relations and the quality of life of both typically developing children and persons with special educational needs, such as visual impaired children. As facial expression of emotions and social skills are profoundly connected, there is the demand of programming interventions directed to maintaining, modulating and enhancing facial expressions topographically and functionally. In order to produce interventions socially valid and effective, planning programs which produce indicators of external and internal validity is of utmost importance. In other words, interventions must be carried out with reliable measures and well-delimited procedures so as the acquired repertoire may be generalized and maintained. In view of social, methodological and empirical issues that underlie those areas (facial expressions and social skills), the present study aimed at evaluating the impact of a program which trained the facial expression of emotions on the social skills repertoire of blind, low vision and sighted children in (1) acquiring, enhancing and maintaining the discrimination of characteristic facial signs of each basic emotion; (2) acquiring, enhancing and maintaining facial expression of basic emotions using photo and video registers; (3) the quality of facial expressions of basic emotions registered by photos; (4) the ability of emotionally express themselves through their face, actions and voice, evaluated by parents and teachers; (5) acquiring, enhancing and maintaining their social skills, according to their self-evaluation, as well as parents and teachers evaluation. A single-case research design with pretest and posttest, multiple probes and replications intra and inter subjects was adopted. Participants were 3 blind children, 3 children with low vision and 3 sighted children. The intervention program was carried out individually and lasted for 21 sessions. Moreover, the evaluation was carried out by 2 judges, the child s parents and teachers and the children themselves. The Social Skills Rating System (SSRS-BR), Checklist for Evaluation and Probe of Emotional Expressiveness, Checklist for Assessing Facial and Emotional Expression, Inventory of Facial Expression of Emotions by Pictures and Films, Protocol for Assessing the Quality of Facial Expression of Emotions, and, Protocol for Emotional Expressiveness Assessment by Facial Expressions and Non-Verbal Components of Emotions were the instruments used for the evaluation. Except for the SSRSBR, all of the instruments were especially created for the present study. Data analysis was carried out as the following: descriptive statistical analysis was performed for each individual (subjects as their own control) and JT Method (clinical significance and reliable change index) was used in order to assess SSRS-BR data. Results indicated that blind, low vision and typically developing children (ordered from the former to the latter) presented more difficulties in discriminating the facial signs characteristic of six basic emotions during the evaluation, which took place prior to the intervention. The percentage of correct answers of all children in the probes after the intervention was between 83,3% and 100%. In addition to that, parents, teachers and judges evaluated the facial expression repertoire of participants as having improved and maintained itself after the intervention, as well as the quality of facial expressiveness. All participants improved their general score in social skills, with some reliable positive changes (improvement) and clinically significant changes, evidencing the enhancement of the participants repertoire observed after the intervention. In summary, the intervention program was effective for improving and maintaining the facial expression of emotions and some classes of social skills, especially those related to emotional expressiveness.